Processing of flat glass - Itybayeva, G.; Bazhenov, G.; Kasenov, A.; Yanushkin, A.; Abishev, K. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article discusses the issues of sheet glass processing and provides information about the application, advantages, disadvantages and technological capabilities. The technological parameters of waterjet processing that affect to the cutting quality: the jet speed, the grain size of the abrasive, the angle of jet inclination, the distance from the nozzle to the treated surface. The water cutting method or waterjet cutting can significantly increase the speed and quality of material cutting. From an economic point of view, the consumption of material and energy is significantly reduced (by 20-30%), due to the use of water energy as the cutting tool in this method. The consumable material is only water and abrasive material. By modeling, when using software, it is proved that during waterjet cutting, lower stresses are formed in the glass compared to mechanical roller cutting, thereby ensuring minimal heat generation and accurate cutting with an edge roughness of Ra 1.6 microns.